2016
DOI: 10.1080/09593330.2016.1167250
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic oxidation of H2S in the gas phase over TiO2-coated glass fiber filter

Abstract: To promote the photocatalytic oxidation (PCO) of hydrogen sulfide (H2S) in the gas phase, TiO2-coated glass fiber filters were packed in an annular photoreactor. Glass fibers coated with TiO2 thin films were characterized structurally and morphologically by field emission gun scanning electron microscopy (FEG-SEM), scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS) and X-ray diffractometry (XRD). Flow rate and H2S inlet concentration were evaluated to determine the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Therefore, O 3 reduction could not be investigated, but neither was it generated. In our earlier research on the lab-and pilot-scales, we reported up to complete (100%) mitigation of O 3 that was naturally in the unirradiated samples [1,2,11].…”
Section: Particulate Mattermentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, O 3 reduction could not be investigated, but neither was it generated. In our earlier research on the lab-and pilot-scales, we reported up to complete (100%) mitigation of O 3 that was naturally in the unirradiated samples [1,2,11].…”
Section: Particulate Mattermentioning
confidence: 79%
“…It is challenging to make an accurate comparison within previous research due to the differences in the TiO 2 coating thicknesses and I (averaging over one vs. three dimensions). Several papers proved the mechanism of H 2 S oxidation with UV-A photocatalysis based on TiO 2 coating [9][10][11]. However, it is not easy to propose an accurate UV dose to mitigate H 2 S based on the currently collected data.…”
Section: Summary Of the Uv-a Photocatalysis Under The Livestock Environmentmentioning
confidence: 99%
“…Therefore, O3 reduction could not be investigated, but neither was it generated. In our earlier research on the lab-and pilot-scales, we reported up to complete (100%) mitigation of O3 that was naturally in the unirradiated samples [1,2,11].…”
Section: Particulate Mattermentioning
confidence: 79%
“…It is challenging to make an accurate comparison within previous research due to the differences in the TiO2 coating thicknesses and I (averaging over one vs. three-dimensions). Several papers proved the mechanism of H2S oxidation with UV-A photocatalysis based on TiO2 coating [9][10][11]. However, it is not easy to propose an accurate UV dose to mitigate H2S based on the currently collected data.…”
Section: Summary Of the Uv-a Photocatalysis Under The Livestock Environmentmentioning
confidence: 99%
See 1 more Smart Citation